Treatment of antineutrophil cytoplasm autoantibody-associated systemic vasculitis: initiatives of the European Community Systemic Vasculitis Clinical Trials Study Group. - Jayne, DR; Rasmussen, N (1997)
The diagnosis, treatment, and monitoring of the primary systemic vasculitides associated with circulating antineutrophil cytoplasm autoantibodies (ANCA) have formed the focus of a multicenter collaborative study. Consensus has been reached on criteria for classification, clinical subgroupings by extent and severity of disease, and "standard" and "best alternative" therapeutic regimens. Two series of randomized controlled trials have been designed; their aims are (1) to harmonize current approaches to treatment and (2) to test the value of newer therapeutic agents. In support of these trials, semiobjective scoring systems have been created and validated, and previous standardization of ANCA serologic and histologic analysis has been adopted. The systems of classification and clinical management described herein represent the recommendations of a multidisciplinary study group that hopes to improve the outcome of patients with primary systemic vasculitis by wide dissemination of the collective experience from interested centers.